Opportunities of Establishment of Destination Management and Marketing Organizations in Bulgaria - Terziev, Venelin; Arabska, Ekaterina (Journal of Economic Development, Environment and People, 2015)
The paper examines tourism sector development in the Republic of Bulgaria in the context of the country’s strategic priorities till 2020 of knowledge-based economy, sustainable growth and smart specialization, the opportunities for its integration with agri-food sector and potential contribution to balanced rural development. The principles and roles of destination management and marketing organizations are discussed and the opportunities for their application in the national conditions are explored. A framework for of establishment, management and functioning of such organizations is proposed based on integrated and participatory approaches, planning, coordination and communication activities, permanent monitoring and controlling.